Assesing Accounting Practices in MSMEs: A Study of BMT Mazaya’s Support Initiatives - Prawestri, Adhelia Desi (Innovative: Journal Of Social Science Research, 2024)
Accounting is a vital component for any business, offering crucial insights into financial performance and management. Effective accounting practices enable businesses to make informed decisions, monitor financial health, and ensure regulatory compliance. This is especially true for Micro, Small, and Medium Enterprises (MSMEs), where strong accounting practices are essential for tracking financial performance, managing cash flow, and driving growth and sustainability. This study examines how MSMEs supported by BMT Mazaya implement accounting practices, exploring the challenges they face and the benefits they derive. The research focuses on understanding how financial record-keeping, advanced accounting knowledge, and enhanced accounting systems under BMT Mazaya's guidance contribute to MSME growth and sustainability. Utilizing convenience sampling, the study gathers primary data through interviews and employs qualitative descriptive analysis. Findings reveal that while most MSMEs engage in financial record-keeping, the variety and completeness of records are inconsistent, and comprehensive financial reports are lacking. To address these challenges, it is crucial to provide targeted support through financial education, affordable accounting tools, and mentorship, with collaborative efforts from government, educational institutions, and the private sector to foster formal accounting practices and enhance transparency, efficiency, and growth.